2009
DOI: 10.2166/wst.2009.239
|View full text |Cite
|
Sign up to set email alerts
|

Economical and technical efficiencies evaluation of full scale piggery wastewater treatment BNR plants

Abstract: A method evaluating the economic efficiency of piggery waste treatment plant based on kinetics for nitrogen removal performances is executed in this study and five full scale plants were evaluated, monitored intensively during one year under steady-state conditions. The performance data from those surveyed plants were recalculated by first-order kinetic equation instead of the Monod's equation, and the nitrogen removal kinetics related with COD/TKN ratios. Two plants adapting two extreme strategies for pre tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The literature on WWTP efficiency has grown in the last few years. Hsiao et al (2007) and Oa et al (2009) investigated the efficiency of treatment of wastewater from pig farms. In particular, using the DEA approach Hsiao et al (2007) showed that most pig farms in Taiwan had decreasing returns to scale; moreover, larger pig farms usually had higher efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on WWTP efficiency has grown in the last few years. Hsiao et al (2007) and Oa et al (2009) investigated the efficiency of treatment of wastewater from pig farms. In particular, using the DEA approach Hsiao et al (2007) showed that most pig farms in Taiwan had decreasing returns to scale; moreover, larger pig farms usually had higher efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%